Development of E-learning-based Social Studies Learning Media for Class VII Semester II Junior High Schools - Ali Rosmandi; Mahdum Mahdum; Henny Indrawati (Journal of Educational Sciences, 2021)
This study aims to determine the validity, practicality, and effectiveness of the development of E-Learning-based IPS learning media for Class VII Semester II SMP. This research was a Research and Development. This research was conducte at SMPN 1 Mandau, Bengkalis Regency. The type of data collected in this study was qualitative data obtained from interviews, observations and expert validity. The assessment of students was carried out through a questionnaire. The object of research in this study was E-Learning-based IPS Learning Media for Class VII Semester II Junior High School using Chamilo 2019 software. The data analysis used qualitative descriptive analysis and quantitative descriptive statistical analysis. The qualitative descriptive analysis technique was used to process data from the test results from media experts and material experts, while quantitative descriptive statistical analysis techniques were used for media assessment by 30 students with the help of SPSS. The results of the study state that e-learning-based social studies learning media are declared valid by media experts and material experts, with a practical level of media use that is practical or easy to use and the effectiveness of appropriate media in learning activities, which can save time and facilitate the preparation of teaching materials.